Dual-stimulus bilayer hydrogel actuators with rapid, reversible, bidirectional bending behaviors. Issue 17 (18th March 2019) - He, Xiaomin; Sun, Yan; Wu, Jiahui; Wang, Yang; Chen, Feng; Fan, Ping; Zhong, Mingqiang; Xiao, Shengwei; Zhang, Dong; Yang, Jintao; Zheng, Jie
Abstract : Bilayer poly( N -isopropylacrylamide)/graphene oxide hydrogels with dual thermo- and near-infrared-responsive properties were prepared by a simple, in situ polymerization centrifugation method. Abstract : Developing new smart hydrogel systems and new fabrication methods is critical for fundamental research and industrial applications, particularly in the intelligent human–machine field, but still faces great challenges. In this work, we present bilayer poly( N -isopropylacrylamide)/graphene oxide (polyNIPAM/GO) hydrogels with dual thermo- and near-infrared (NIR)-responsive properties using a simple, in situ polymerization-centrifugation method. By tuning the GO concentration and centrifugation speed, a transparent polyNIPAM layer and a dark-brown GO-rich layer are formed, where each layer displays distinct network structures and swelling behavior. Due to the asymmetric double-layer structure, the polyNIPAM/GO bilayer hydrogels enable one to realize fast, controllable, bidirectional bending under thermal or NIR stimulation within 1 min, and the bending orientation and degree can be reversibly, repeatedly, and precisely controlled by the temperature- or NIR-induced cooperative swelling–shrinking properties of both layers. Based on the reversible, bi-directional bending nature of polyNIPAM/GO hydrogels, we further design two proof-of-concept hydrogel actuators to highlight the advantages of this hydrogel system: one acts as a wiggler to mimic robot arms to move objects, while the other serves as an electric switch to turn on/off a light. In addition, our polymerization-centrifugation method can also be used to prepare polyNIPAM/SiO2 bilayer hydrogels, demonstrating its general applicability to other polyNIPAM–nanoparticle hydrogels with a bilayer structure. This work provides both a new fabrication method and hybrid hydrogel systems for the development of smart, programmable, and versatile hydrogel-based actuators.